Patrimônio Paleontológico: ressonância e encantamento - Siciliano, Mell (2023)
There are several works that deal with the relationship between local communities and heritage, with the most varied approaches; in the specific case of paleontological heritage, there is a growing concern about this topic. Considering that, in general, initiatives for the preservation of paleontological heritage are mobilized by the academic community, this thesis arises from concerns about the relationship established between fossils institutionalized as paleontological heritage and local communities that live daily with this heritage, in particular the ones preserved by the geoconservation initiative called geopark, since community participation is seen as essential in such spaces. The proposal is to investigate this relationship using the notions of resonance and wonder, envisioning the possibility of measuring the established relationships to better understand them. The research was divided into two stages, theoretical research, and field work. The field work was developed in the surrounding area of two geosites of the Uberaba Geopark – Land of Giants. This geopark is important from a scientific point of view as it encompasses an important geological feature: the Bauru Basin. From a sociocultural point of view, the space becomes interesting as it is a geopark still under development. The results show that, in general, the local communities investigated do establish relationships with the local paleontological heritage, with different levels of understanding of what this heritage would be, and also different levels of involvement. The notions of resonance and wonder proved to be useful for understanding the relationships established, as it opened the possibility to typify them, making it easier to understand such a complex reality, and showing potential for applicability in other contexts.